Design of Novel, Water Soluble and Highly Luminescent Europium Labels with Potential to Enhance Immunoassay Sensitivities - Henri Sund; Kaj Blomberg; Niko Meltola; Harri Takalo (Molecules, 2017)
To meet the continual demands of more-sensitive immunoassays, the synthesis of novel luminescent Eu(III) chelate labels having similar substituted 4-(phenylethynyl)pyridine chromophores in three different chelate structure classes are reported. Significantly enhanced luminescence intensities were obtained, evidently caused by the intra-ligand charge transfer (ILCT) mediated sensitization, but the alternative ligands triplet state process cannot be ruled out. Based on the present study, even quite small changes on the chelate structure, and, especially, on the substituents’ donor/acceptor strength on both ends of 4-(phenylethynyl)pyridine subunits have an unpredictable effect on the luminescence. The highest observed brightness was 16,400 M−1cm−1 in solution and 69,500 M−1cm−1 on dry surface, being 3.4 and 8.7 fold higher compared to the reference chelate. The new label chelates provide solutions for improved assay sensitivity up-to tenfold from the present concepts.